2007
DOI: 10.1158/1078-0432.ccr-06-2700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tibolone on Breast Cancer Cell Proliferation in Postmenopausal ER+ Patients: Results from STEM Trial

Abstract: Purpose: Tibolone is a selective tissue estrogenic activity regulator, approved for the treatment of vasomotor symptoms in postmenopausal women.We have done an exploratory, double-blind, randomized, placebo-controlled pilot trial to investigate the tissue-specific effects of 2.5 mg tibolone on breast cancer in postmenopausal women, in particular on tissue proliferation (STEM, Study of Tibolone Effects on Mamma carcinoma tissue). Experimental Design: Postmenopausal women with initially stage I/II, estrogen rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…De forma semelhante, os dados encontrados neste estudo não revelaram alterações proliferativas significantes em nenhum dos intervalos de tratamento avaliados. Kubista et al 34 também demostraram que a tibolona não apresentou efeito sobre a proliferação celular em pacientes com câncer de mama primário ER positivo. Já diretamente sobre as células tumorais a droga esteve associada à elevação nos índices de marcadores de apoptose e à redução da atividade proliferativa dessas células 35 .…”
Section: Discussionunclassified
“…De forma semelhante, os dados encontrados neste estudo não revelaram alterações proliferativas significantes em nenhum dos intervalos de tratamento avaliados. Kubista et al 34 também demostraram que a tibolona não apresentou efeito sobre a proliferação celular em pacientes com câncer de mama primário ER positivo. Já diretamente sobre as células tumorais a droga esteve associada à elevação nos índices de marcadores de apoptose e à redução da atividade proliferativa dessas células 35 .…”
Section: Discussionunclassified
“…In addition, tibolone slows down the proliferation rate of breast cancer cells in vitro and in clinical studies, as well as increasing differentiation and apoptosis [33,41,44,45] . In normal breast cells, it was also reported that tibolone and its 4-ene isomer have antiproliferative and proapoptotic activities, partly due to inhibiting bcl-2 expression and inducing oxidative 17 β -HSD activity [37,46] .…”
Section: Discussionmentioning
confidence: 99%
“…No increase in proliferation was seen in the tibolone or placebo group, whereas a significant increase was observed in the oestradiol/norethisterone acetate group (Conner et al 2004 ). This was further investigated in a randomised, placebo-controlled study in patients with oestrogen receptor-positive primary breast cancer (Kubista et al 2007 ). However, the treatment duration was only 14 days and only a trend of a beneficial effect on proliferation was observed.…”
Section: Treatment With Synthetic Compounds With Partial Estrogenic Amentioning
confidence: 99%